Effect of DGAT1, FASN and PRL genes on milk production and milk composition traits in Simmental and crossbred Holstein cattle - MAURIÆ, MAJA; MAŠEK, TOMISLAV; BENIÆ, MIROSLAV; ŠPEHAR, MARIJA; STARÈEVIÆ, KRISTINA (The Indian Journal of Animal Sciences, 2017)
The aim of this study was to evaluate the effects of polymorphisms in the acylCoA diacylglycerol acyltransferase (DGAT1), fatty acid synthase (FASN) and prolactin (PRL) genes on milk production traits and the potential influence of the PRL gene on SCC of Simmental and crossbred Holstein cattle as well as comparatively among them. A total of eighty-three cows were genotyped by PCR-RFLP method. Crossbred Holsteins with DGAT1 genotype KA hadsignificantly higher fat content than cows with AA genotype and for FASN diplotype TW/AR had significantly higher fat content compared to diplotype AR/AR. In the observed group of animals, there was no association found between PRL SNP G8398A and milk production traits and SCC (SCS). For all three genes, cross bred Holstein hadsignificantly higher milk yield, fat and protein content in certain genotypes/diplotypes. The results of combined genotype analysis of the three SNPs showed that GG/TWAR/KK genotype combination had the lowest SCS.